Impact of the Friendly Schools whole-school intervention on transition to secondary school and adolescent bullying behaviour - Cross, D.; Shaw, T.; Epstein, M.; Pearce, N.; Barnes, A.; Burns, Sharyn; Waters, S.; Lester, L.; Runions, K. (2018)
© 2018 John Wiley & Sons Ltd Peer bullying increases in times of school transition, influenced by changing peer and friendship groups, new schooling environments and greater stress. Covert forms of bullying, including cyberbullying, become more common in secondary school and cause considerable distress and long-term harm. The period of transition to secondary school is therefore a critical window for intervening to manage and prevent bullying. A three-year cluster randomised control trial was conducted to develop, implement and evaluate the Friendly Schools Project intervention which aimed to reduce bullying and aggression among more than 3,000 students who had recently transitioned to secondary school. Intervention schools were provided with individualised training and resources to support students’ transition and reduce bullying using a multi-level comprehensive intervention addressing classroom curriculum, school policies and procedures, the social and physical environment, pastoral care approaches and school-home-community links. Although the observed effect sizes were small, the intervention had a consistently significant positive effect across a range of outcomes, including bullying perpetration, victimisation, depression, anxiety, stress, feelings of loneliness and perceptions of school safety at the end of the students’ first year in secondary school. However, none of these differences were sustained into the students’ second year of secondary school. These findings demonstrate the immediate value of whole-school interventions to reduce bullying behaviour and associated harms among students who have recently transitioned to secondary school, as well as the need to provide strategies that continue to support students as they progress through school, to sustain these effects.